INTEGRASI SOSIO-KULTURAL MASYARAKAT PESISIR DI KELURAHAN BAURUNG KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE - Rahmatullah; Husniah (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2025)
This paper discusses the socio-cultural integration of coastal communities in Baurung Village, East Banggae District, Majene Regency. This paper aims to analyze the forms of socio-cultural integration of coastal communities in Baurung Village, East Banggae District, Majene Regency. In this paper, the author has the main focus of his study on social interaction, local cultural values and socio-cultural integration and adaptation between ethnic groups that live side by side in the area. This paper uses a qualitative approach using descriptive methods, data obtained through field observations conducted by researchers in the Baurung Village area. Then conducting in-depth interviews with the Baurung Village community and conducting documentation. The results of this study indicate that socio-cultural integration in Baurung Village can be seen from the existence of events or traditions such as the celebration of the fisherman's party (Mappasso), mutual cooperation (Sirondo-rondoi), social services, buying and selling activities and so on. From several of these activities, the involvement of several individual actors who interact with each other in a structured manner has a match with the structural functionalism theory put forward by Talcott Parson. The factors that drive socio-cultural integration are the adaptation of existing values that are still believed in by the community, tolerance between coastal community groups, and collective participation in social, cultural and religious activities.